The challenges of ethics and entrepreneurship in the global environment - Hoskinson, Sherry; Kuratko, Donald F.; Emerald eBooks (Bingley, U.K. : Emerald, 2015)
This is the 25th volume in the Advances in the study of entrepreneurship, innovation, and economic growth, which has led the field with insightful and forward looking perspectives on topics for 25 years. Papers in this volume focus on topics, perspectives, challenges, and visions of scholars in the area of entrepreneurship as well as in ethics in light of dramatic changes across the global environment of entrepreneurship and innovation. This volume builds a body of scholarship specific to ethics and entrepreneurship by providing the latest perspectives on how ethics is impacted by or impacting the entrepreneurship field. Scholars examine the most current topics, perspectives, challenges, and visions in the area of ethics and entrepreneurship and reflect the sense of urgency and commitment to creating a generation of ethical entrepreneurial leaders. The contributors have created a framework for the ethical challenges involved with entrepreneurship and innovation within today's global environment.
Entrepreneurship and existentialism : establishing authenticity in a crowded global marketplace / Michael G. Goldsby, Robert Mathews -- The entrepreneur's dilemma of ethics versus professional acceptability with online reputation management systems / Donald F. Kuratko, Travis J. Brown, Marcus Wadell -- The ethical pitfalls and opportunities of initial public offerings / Abbey Stemler, Timothy L. Fort -- The ethics of guerilla behavior in early stage firms / Yongseok Jang, Michael H. Morris -- Questioning the ethics of university entrepreneurship curriculum / Allan O'Connor -- Curricular and programmatic innovation at the intersection of business ethics and entrepreneurship / Chris Fawson, Randy Simmons, Ryan Yonk.
Keywords: Business & Economics -- Entrepreneurship; Entrepreneurship; Business ethics; Entrepreneurship; Electronic books